2019
DOI: 10.4081/mrm.2019.484
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and management of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal interstitial lung disease (ILD) with an unpredictable clinical course. Although IPF is rare, healthcare professionals should consider IPF as a potential cause of unexplained chronic dyspnea and/or cough in middle-aged/elderly patients and refer patients to a pulmonologist for evaluation. Making a diagnosis of IPF requires specialist expertise. Multidisciplinary discussion, involving at minimum a pulmonologist and a radiologist with expertise in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Healthcare systems deal differently with diagnostic possibilities and availability. Considering treatment, expensive therapies are often introduced later as in wealthier countries and might be limited to a selected population of IPF ( 14 , 15 ). Many off-label treatments are applied in rare diseases with potentially serious side effects ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare systems deal differently with diagnostic possibilities and availability. Considering treatment, expensive therapies are often introduced later as in wealthier countries and might be limited to a selected population of IPF ( 14 , 15 ). Many off-label treatments are applied in rare diseases with potentially serious side effects ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, RDNs can address nutrition issues while providing credible, evidence‐based recommendations to patients with ILD. Previous research has identified patient education, symptom relief, and management of comorbidities as vital components of supportive care in ILD management 90 . RDNs can support patients in each of these three supportive care components using their nutrition expertise and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events are the most common reason for patients to discontinue medications 89 . In general, medication‐related gastrointestinal (GI) adverse events can be managed through dose adjustment, treatment interruption, and/or symptoms management 90 . Therefore, involvement of healthcare professionals to provide symptomatic and supportive care to patients in order to manage these medication‐related adverse events is an important component of ILD/IPF management.…”
Section: Other Nutrition Concernsmentioning
confidence: 99%
“…Evidence throughout the literature provided by Quinn, Wisse, & Manns, (2019) [17], also highlights the efficacy and significance of pulmonary rehabilitation in patients suffering from shortness of breath due to pulmonary fibrosis and associated complications. It has been found that pulmonary rehabilitation is considered to be one of the prime critical care management strategies in case of permanent fibrosis as it provides significant knowledge and information to the patients regarding their health condition as well as the procedures they need to maintain to restore their health [18].…”
Section: Theme -2 Physical Activity and Pulmonary Rehabilitationmentioning
confidence: 97%